DNA methylation of the glucocorticoid receptor gene promoter in the placenta is associated with blood pressure regulation in human pregnancy. Issue 11 (November 2017) - Dwi Putra, Sulistyo E.; Reichetzeder, Christoph; Meixner, Martin; Liere, Karsten; Slowinski, Torsten; Hocher, Berthold
Abstract : Background: Blood pressure (BP) regulation during pregnancy is influenced by hormones of placental origin. It was shown that the glucocorticoid system is altered in hypertensive pregnancy disorders such as preeclampsia. Epigenetic mechanism might influence the activity of genes involved in placental hormone/hormone receptor synthesis/action during pregnancy. Method: In the current study, we analyzed the association of 5′-C-phosphate-G-3′ (CpG) site methylation of different glucocorticoid receptor gene ( NR3C1 ) promoter regions with BP during pregnancy. The study was performed as a nested case-control study ( n = 80) out of 1045 mother/child pairs from the Berlin Birth Cohort. Placental DNA was extracted and bisulfite converted. Nested PCR products from six NR3C1 proximal promoter regions [glucocorticoid receptor gene promotor region B (GR-1B), C (GR-1C), D (GR-1D), E (GR-1E), F (GR-1F), and H (GR-1H)] were analyzed by next generation sequencing. Results: NR3C1 promoter regions GR-1D and GR-1E had a much higher degree of DNA methylation as compared to GR-1B, GR-1F or GR-1H when analyzing the entire study population. Comparison of placental NR3C1 CpG site methylation among hypotensive, normotensive and hypertensive mothers revealed several differently methylated CpG sites in the GR-1F promoter region only. Both hypertension and hypotension were associated with increased DNA methylation of GR-1F CpG sites. These associations were independent of confounding factors, such as family history of hypertension, smoking status before pregnancy and prepregnancy BMI. Assessment of placental glucocorticoid receptor expression by western blot showed that observed DNA methylation differences were not associated with altered levels of placental glucocorticoid receptor expression. However, correlation matrices of all NR3C1 proximal promoter regions demonstrated different correlation patterns of intraregional and interregional DNA methylation in the three BP groups, putatively indicating altered transcriptional control of glucocorticoid receptor isoforms. Conclusion: Our study provides evidence of an independent association between placental NR3C1 proximal promoter methylation and maternal BP. Furthermore, we observed different patterns of NR3C1 promoter methylation in normotensive, hypertensive and hypotensive pregnancy. Abstract : Supplemental Digital Content is available in the text